2020
DOI: 10.21203/rs.2.17238/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The predictive value of lymphocyte-to-monocyte ratio in the prognosis of acute coronary syndrome patients: A systematic review and meta-analysis

Abstract: Background: The association between the lymphocyte-to-monocyte ratio (LMR) and prognosis in the patients with acute coronary syndrome (ACS) is not fully understood. We performed this systematic review and meta-analysis to evaluate the correlation between LMR and mortality or major adverse cardiac events (MACE) in patients with ACS. Methods: A systematic search was performed in MEDLINE, Web of science, EMBASE, Scopus, and the Cochrane Library. The association between LMR and mortality/MACE was analyzed in patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…34 Previous research has found a link between progression, in-hospital mortality rates, and prognosis of cardiovascular diseases and the MLR. [35][36][37] Previous studies also confirmed the strong link of monocyte counts with the severity of atherosclerosis and the size of a myocardial infarction. [38][39][40]…”
Section: Discussionmentioning
confidence: 64%
“…34 Previous research has found a link between progression, in-hospital mortality rates, and prognosis of cardiovascular diseases and the MLR. [35][36][37] Previous studies also confirmed the strong link of monocyte counts with the severity of atherosclerosis and the size of a myocardial infarction. [38][39][40]…”
Section: Discussionmentioning
confidence: 64%